The Purchase of Intimacy - Zelizer, Viviana A. Rotman (Book collections on Project MUSE., 2005)
In their personal lives, people consider it essential to separate economics and intimacy. We have, for example, a long-standing taboo against workplace romance, while we see marital love as different from prostitution because it is not a fundamentally financial exchange. In The Purchase of Intimacy, Viviana Zelizer mounts a provocative challenge to this view. Getting to the heart of one of life's greatest taboos, she shows how we all use economic activity to create, maintain, and renegotiate important ties--especially intimate ties--to other people. In everyday life, we invest intense effort a.